Biodiversity footprint assessment of VTT - Pöyhönen, Jaakko; Räisänen, Eetu (2024)
Biodiversity loss is one of the greatest environmental threats. The importance of biodiversity for people, societies and businesses cannot be overstated. It is therefore important to be able to assess the human-caused biodiversity impacts and how to mitigate them. Based on the direct drivers of biodiversity loss, it is possible to assess the biodiversity footprint of different organizations. In our work, we assess VTT's biodiversity footprint using the method developed by researchers at the University of Jyväskylä. Our aim is to assess the total biodi-versity footprint of VTT, the most material activities causing it, how to reduce the biodiversity footprint and what other organizational improvements could be done. We will also look into what extent the methodology developed by re-searchers of University of Jyväskylä can be applied to the Science Based Tar-gets for Nature framework. VTT's total biodiversity footprint in 2022 was 105,73 nBDe, most of which was generated by district heating, business services, machinery and equip-ment. Potential targets for reducing the biodiversity footprint include reducing the share of bio-based fuels for energy, avoiding or minimizing the share of biodiversity intensive activities and seeking to reduce the volume of harmful activities. Organizational improvements are related to financial and environ-mental accounting, which could help to build a more efficient system for as-sessing the biodiversity footprint in the future. Regarding the comparison of two frameworks, the method developed by researchers at the University of Jyväskylä is suitable for Step 1 and partly Step 2 of the SBTN framework. The results of this study provide valuable insight into the biodiversity im-pacts of a research organization and what they are composed of. The results will allow us to identify areas of refinement in the methodology we use, which could provide more accurate information on the biodiversity impacts of specif-ic procurements. The applicability of the biodiversity footprint method devel-oped by researchers at the University of Jyväskylä also opens up new opportu-nities for organizations to adopt the SBTN framework.